Exciton-coupled charge-transfer dynamics in a porphyrin J-aggregate/TiO 2 complex - Verma, Sandeep; Ghosh, Amrita; Das, Amitava; Ghosh, Hirendra Nath (Chemistry a European Journal, 2011)
Exciton-coupled charge-transfer (CT) dynamics in TiO2 nanoparticles (NP) sensitized with porphyrin J-aggregates has been studied by femtosecond time-resolved transient absorption spectroscopy. J-aggregates of 5,10,15-triphenyl-20-(3,4-dihydroxyphenyl) porphyrin (TPPcat) form CT complexes on TiO2 NP surfaces. Catechol-mediated strong CT coupling between J-aggregate and TiO2 NP facilitates interfacial exciton dissociation for electron injection into the conduction band of the TiO2 nanoparticle in pulse width limited time (<80 fs). Here, the electron-transfer (<80 fs) process dominates over the intrinsic exciton-relaxation process (J-aggregates: ca. 200 fs) on account of exciton-coupled CT interaction. The parent hole on J-aggregates is delocalized through J-aggregate excitonic coherence. As a result, holes immobilized on J-aggregates are spatially less accessible to electrons injected into TiO2, and thus the back electron transfer (BET) process is slower than that of the monomer/TiO2 system. The J-aggregate/porphyrin system shows exciton spectral and temporal properties for better charge separation in strongly coupled composite systems.

Interfacial electron transfer dynamics of two newly synthesized catecholate bound ruII polypyridyl-based sensitizers on TiO2 nanoparticle surface - a femtosecond pump probe spectroscopic study - Banerjee, Tanmay; Rawalekar, Sachin; Das, Amitava; Ghosh, Hirendra Nath (Europian Journal of Inorganic Chemistry, 2011)
Two new catecholate-bound RuII–polypyridine based sensitizers, (2,2′-bipyridine){ethyl 3-(4-hydroxyphenyl)-2-[(4′-methyl-2,2′-bipyridinyl-4-carbonyl)amino]propionate}{4-[2-(4′-methyl-2,2′-bipyridinyl-4-yl)vinyl]benzene-1,2-diol)}ruthenium(II) hexafluorophosphate (5) and [(2,2′-bipyridine)-(4-2,2′-bipyridinyl-4-yl-phenol)-(4-{2-(4′-methyl-2,2′-bipyridinyl-4-yl)vinyl}benzene-1,2-diol)]ruthenium(II) hexafluorophosphate (6) with secondary electron-donating groups (tyrosine and phenol, respectively) were synthesized and characterized. Steady-state optical absorption and emission studies confirm strong coupling between the sensitizers and TiO2 nanoparticles. Femtosecond visible transient absorption spectroscopy has been employed to study interfacial electron transfer (IET) dynamics in the dye–nanoparticle systems to explore the influence of the secondary electron-donating groups on IET dynamics. Electron injection into the conduction band of nanoparticulate TiO2 has been confirmed by detection of the conduction band electrons in TiO2 ([e–]TiO2CB) and radical cation of the adsorbed dye (D·+) in real time monitored by transient absorption spectroscopy. A single exponential and pulse-width limited (< 100 fs) electron injection has been observed. Back electron transfer (BET) dynamics have been studied by monitoring the decay kinetics of the injected electron in the conduction band of TiO2 and by the recovery of the ground state bleach. BET dynamics in dye–TiO2 systems for complexes 5 and 6 have been compared with those of [bis(2,2′-bpy)-(4-{2-(4′-methyl-2,2′-bipyridinyl-4-yl)vinyl}benzene-1,2-diol)]ruthenium(II) hexafluorophosphate (7), which does not have a secondary electron-donating group.

Photophysical properties of ligand localized excited state in ruthenium(ii) polypyridyl complexes: a combined effect of electron donor-acceptor ligand - Verma, Sandeep; Kar, Prasenjit; Das, Amitava; Ghosh, Hirendra Nath (Dalton Trans, 2011)
We have synthesized ruthenium(II) polypyridyl complexes (1) Ru(II)(bpy)2(L1), (2) Ru(II)(bpy)2(L2) and (3) Ru(II)(bpy)(L1)(L2), where bpy = 2,2′-bipyridyl, L1 = 4-[2-(4′-methyl-2,2′-bipyridinyl-4-yl)vinyl]benzene-1,2-diol) and L2 = 4-(N,N-dimethylamino-phenyl)-(2,2′-bipyridine) and investigated the intra-ligand charge transfer (ILCT) and ligand–ligand charge transfer (LLCT) states by optical absorption and emission studies. Our studies show that the presence of electron donating –NMe2 functionality in L2 and electron withdrawing catechol fragment in L1 ligands of complex 3 introduces low energy LLCT excited states to aboriginal MLCT states. The superimposed LLCT and MLCT state produces redshift and broadening in the optical absorption spectra of complex 3 in comparison to complexes 1 and 2. The emission quantum yield of complex 3 is observed to be extremely low in comparison to that of complex 1 and 2 at room temperature. This is attributed to quenching of the 3MLCT state by the low-emissive 3LLCT state. The emission due to ligand localized CT state (ILCT and LLCT) of complexes 2 and 3 is revealed at 77 K in the form of a new luminescence band which appeared in the 670–760 nm region. The LLCT excited state of complex 3 is populated either via direct photoexcitation in the LLCT absorption band (350–700 nm) or through internal conversion from the photoexcited 3MLCT (400–600 nm) states. The internal conversion rate is determined by quenching of the 3MLCT state in a time resolved emission study. The internal conversion to LLCT and ILCT excited states are observed to be as fast as ∼200 ps and ∼700 ps for complexes 3 and 2, respectively. The present study illustrates the photophysical property of the ligand localized excited state of newly synthesized heteroleptic ruthenium(II) polypyridyl complexes.

Newly designed resorcinolate binding for Ru(II)- and Re(I)- polypyridyl complexes on oleic acid capped tio2 in non-aqueous solvent: prolonged charge separation and substantial thermalized 3MLCT injection - Banerjee, Tanmay; Kaniyankandy, Sreejith; Das, Amitava; Ghosh, Hirendra Nath (Journal of Physical Chemistry C, 2013)
Femtosecond pump–probe spectroscopic studies on a series of newly synthesized resorcinol-based Ru(II) and Re(I) complexes on oleic acid capped TiO2 nanoparticles have been carried out in chloroform, and the results are compared with those of the catechol analogues. The ruthenium complex shows biexponential injection; the second component arises due to injection from the thermally equilibrated 3MLCT states as a result of a weaker strength of the resorcinolate binding. Also, in comparison with catechol binding, as a result of a greater diffusion of the injected electrons into TiO2, the back electron transfer (BET) is slowed down significantly for the ruthenium complex. These are distinctive observations for any mononuclear ruthenium–polypyridyl–enediol complex reported thus far. However, the rhenium complex educes single exponential ultrafast injection (<120 fs) because of apparent injection in a high density of states and shows the most prominent results with ∼50% slowdown in the charge recombination rate as compared to the analogous catechol bound system. These results exemplify the probable development of highly capable sensitizer dyes with resorcinol as the anchoring group for the development of efficient dye-sensitized solar cells.

Synthesis, steady-state, and femtosecond transient absorption studies of resorcinol bound ruthenium(ii)- and osmium(ii)-polypyridyl complexes on nano-TiO2 surface in water - Banerjee, Tanmay; Kaniyankandy, Sreejith; Das, Amitava; Ghosh, Hirendra Nath (Inorganic Chemistry, 2013)
The synthesis of two new ruthenium(II)- and osmium(II)-polypyridyl complexes 3 and 4, respectively, with resorcinol as the enediol anchoring moiety, is described. Steady-state photochemical and electrochemical studies of the two sensitizer dyes confirm strong binding of the dyes to TiO2 in water. Femtosecond transient absorption studies have been carried out on the dye–TiO2 systems in water to reveal <120 fs and 1.5 ps electron injection times along with 30% slower back electron transfer time for the ruthenium complex 3. However, the corresponding osmium complex 4 shows strikingly different behavior for which only a <120 fs ultrafast injection is observed. Most remarkably, the back electron transfer is faster as compared to the corresponding catechol analogue of the dye. The origin and the consequences of such profound effects on the ultrafast interfacial dynamics are discussed. This Article on the electron transfer dynamics of the aforesaid systems reinforces the possibility of resorcinol being explored and developed as an extremely efficient binding moiety for use in dye-sensitized solar cells.

New Ru(II)/Os(II)-polypyridyl complexes for coupling to TiO2 surfaces through acetylacetone functionality and studies on interfacial electron-transfer dynamics - Banerjee, Tanmay; Biswas, Abul Kalam; Sahu, Tuhin Subhra; Ganguly, Bishwajit; Das, Amitava; Ghosh, Hirendra Nath (Dalton Transactions, 2014)
New Ru(II)- and Os(II)-polypyridyl complexes have been synthesized with pendant acetylacetone (acac) functionality for anchoring on nanoparticulate TiO2 surfaces with a goal of developing an alternate sensitizer that could be utilized for designing an efficient dye-sensitized solar cell (DSSC). Time-resolved transient absorption spectroscopic studies in the femtosecond time domain have been carried out. The charge recombination rates are observed to be very slow, compared with those for strongly coupled dye molecules having catechol as the anchoring functionality. The results of such studies reveal that electron-injection rates from the metal complex-based LUMO to the conduction band of TiO2 are faster than one would expect for an analogous complex in which the chromophoric core and the anchoring moiety are separated with multiple saturated C-C linkages. Such an observation is rationalized based on computational studies, and a relatively smaller spatial distance between the dye LUMO and the TiO2 surface accounted for this. Results of this study are compared with those for analogous complexes having a gem-dicarboxy group as the anchoring functionality for covalent binding to the TiO2 surface to compare the role of binding functionalities on electron-transfer dynamics.

Superior grafting and state-of-the-art interfacial electron transfer rates for newly designed geminal dicarboxylate bound ruthenium(II)- and osmium(II)-polypyridyl dyes on TiO2 nanosurface - Banerjee, Tanmay; Biswas, Abul Kalam; Reddy, Upendar G.; Sahu, Tuhin Subhra; Das, Amitava; Ganguly, Bishwajit; Ghosh, Hirendra Nath (Journal of Physical Chemistry C, 2014)
Two new Ru(II)-/Os(II)-polypyridyl based sensitizer dyes with geminal dicarboxylic acid group as the binding unit for superior grafting of the dye to TiO2 have been designed and synthesized. Steady-state photochemical studies of the two sensitizer dyes in presence of TiO2 in water confirm strong binding of the dyes to TiO2. Femtosecond transient absorption studies of these newly synthesized dyes on TiO2 nanosurface have been carried out in water and the results have been compared with those for the corresponding 4,4'-dicarboxy-2,2'-bipyridine analogues of the dyes. While the charge recombination rates are considerably slower, interestingly, the electron injection rates are very fast for multiple saturated C-C linkages present between the chromophoric core and the anchoring moiety. The origin and the consequences of such profound effects on the ultrafast interfacial dynamics are discussed. This is the first report on the ultrafast transient absorption studies of dyes with geminal dicarboxylic acid binding groups, which we believe will add significantly to the present research efforts toward the development of robust and efficient dyes for use in dye solar applications.